PERUMUSAN, FORMULASI, DAN ADOPSI KEBIJAKAN PENDIDIKAN - Haditsa Qur'ani Nurhakim; Arif Rahman Hakim; Basuki; Mamat Rahmat; Supiana; Qiqi Yuliati Zakiah (LPPM STAI Muhammadiyah Probolinggo, 2025)
Educational policy serves as a strategic foundation in national development, as it directly influences the quality of human resources produced. This article comprehensively examines three key aspects within the realm of public policy, namely problem formulation, educational policy formulation, and policy adoption. The method employed in this study is a literature review. In the problem formulation stage, emphasis is placed on the importance of accurately and systematically identifying issues so that the resulting policies are relevant to societal needs and capable of addressing contemporary challenges. Furthermore, policy formulation is analyzed by considering the role of internal and external factors, the application of policy theories, as well as the contributions of various actors involved in the process of drafting and establishing educational policies. In terms of policy adoption, this article reviews best practices from countries with excellent education systems, such as Finland, Japan, and South Korea, while also exploring the potential for their implementation in the Indonesian context. The integration of these three aspects is expected to foster educational policies that are more adaptive, democratic, inclusive, and oriented toward the sustainable improvement of human resource quality.